International mergers and trade liberalisation : implications for unionised labour - Straume, Odd Rune (2003)
An international oligopoly model with unionised and non-unionised firms is constructed to make predictions about the pattern of international mergers. Applying the method of endogenous merger formation developed by Horn and Persson [International Journal of Industrial Organisation 19 (2001) 1213] we find that the equilibrium market structure is highly dependent on the level of trade costs. The model is further utilised to analyse the implications of trade liberalisation for unionised labour. A main finding is that, for sufficiently high levels of trade costs, unionised workers may benefit from a merger between non-unionised firms, whereas low levels of trade costs make unionised firms highly ‘vulnerable’ to an international merger, which could be detrimental to the union’s ability to capture oligopoly rents.